Oxidative Stress in Primary Infertility of Women (Global Journal of Medical Research, 2013)
The current study was designed to investigate the changes of oxidative stress (OS) in primary infertility of females. To achieve the intended aim, 84 infertile women of ages 28.66 ± 6.29 years (mean ± SD) and 30 healthy fertile women of ages 30.3± 6.45 years (mean±SD) were enrolled. The levels of malondialdehyde (MDA), catalase (CAT) and glutathione-S-transferase (GST) were determined by spectrophotometric methods. Serum follicule stimulating hormone (FSH) and luteinizing hormone (LH) levels were measured by an enzyme linked fluorescent assay (ELFA). The results indicated a significant (p